Basis for the formation of media anthropology in Сhina (philosophical and anthropological analysis) - Dezhong, Wang (Видавничий дім "Гельветика", 2022)
Due to the development of media resources, the influence of the Internet in China has led to significant changes in all spheres of life. As a result of the widespread use of media, we have witnessed changes in culture, lifestyles and individuals. Through analyzing the current media culture in China, we have concluded that the media has had a significant impact on education, democracy, aesthetics, literature, language and communication. Through media, human problems are exacerbated. Examples include, dependency on online media leading to the loss of subjectivity, excessive information without classification resulting in the “disappearance of childhood”, online media affecting the socialization of adolescents, etc. By examining media culture, we can say that a new philosophical orientation has been establishing in China, namely media anthropology, which focuses on the impact of media culture on people, both in virtual and real life. This is evidenced by the latest data from scientific publications. Turning to research in the field of philosophy, sociology, cultural studies, education and adding an ethnographic method, we analyzed the specifics of media culture in China and came to the following conclusions. First, the historicity and humanity of traditional culture have been transformed. Moreover, the value of culture has been disparaged due to the unconscious influence of online entertainment and the general commercial nature of network platforms. Second, people have accustomed themselves to communicating via online media in China. Yet this virtual communication eliminates the emotional component, leaving only instantaneous text input. Hence, by trying to maintain digital social contact, people have “fallen” into social dependence, and leading to exhaustion. Researchers have also noted that online reading is beginning to dominate over paper reading, especially for the younger generation. Because online media is extraordinarily complicated, mixed with images, colors, animation, and other elements, it distracts and prevents the reader from focusing on the content, as well as disrupting logical reading. Thus, under these new conditions of existence man’s issues are discussed under the direction of such philosophy as philosophical media anthropology.
Keywords: media culture; media anthropology; modern China; human problem; cyberspace; network society; Internet; traditions; culture